Pengembangan Tugas Autentik Pada Pembelajaran Matematika Model GI-TTW Untuk Meningkatkan Kreativitas Siswa - Zahroh, Alfiatuz; Pradita, Mutiea Ira (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
ABSTRACT: The purpose of this study was to develop an authentic task based on the GI-TTW (Group Investigation–Think Talk Write) model to enhance students’ creativity. This research employed the Research and Development (R&D) method using the Plomp development model, which consists of three stages: (1) preliminary research, including problem analysis and material analysis; (2) prototyping phase, involving the development of authentic tasks in the form of LKPD (student worksheets), pretest and posttest instruments, validity instruments, and practicality questionnaires; and (3) assessment phase, which includes the validation, practicality, and effectiveness testing of the product. The research subjects were students of class XI-B at SMA Hang Tuah 4 Surabaya. The validation results showed a score of 83% from content experts and 85% from design experts, indicating that the developed product falls into the